The Role of Digital Technologies in Growing Secondary School Students to the Profession - Rasulov Inom Muydinovich (Genius Publishing Group, 2022)
This article discusses the role of digital technologies in attracting secondary school students to the profession. In our country, as in many other countries, there is no largescale system for assessing the quality and selection of digital resources for education. This means that a variety of digital tools with various positive and negative properties can be at the disposal of teachers. Under these conditions, a modern teacher cannot but be partly an expert, able to independently identify ineffective digital tools.
Keywords: Digital technology; informatics; pedagogy; methodology